2013
DOI: 10.1099/ijs.0.043596-0
|View full text |Cite
|
Sign up to set email alerts
|

Polycladomyces abyssicola gen. nov., sp. nov., a thermophilic filamentous bacterium isolated from hemipelagic sediment

Abstract: A novel filamentous bacterium, designated strain JIR-001T, was isolated from hemipelagic sediment in deep seawater. This strain was non-motile, Gram-positive, aerobic, heterotrophic and thermophilic; colonies were of infinite form and ivory coloured with wrinkles between the centre and the edge of the colony on ISP2 medium. The isolate grew aerobically at 55–73 °C with the formation of aerial mycelia; spores were produced singly along the aerial mycelium. These morphological features show some similarities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…L. sacchari LP175 showed substantial growth on NA with added cellulose, inositol, raffinose, rhamnose and sucrose; however, no growth was evident for L. sacchari comb. nov.. Isolates C77, C79, C86, C88, C89, K25 and KT176 showed 99.7% similarity with the filamentous bacteria, Polycladomyces abyssicola JIR-001 T , a novel genus which was recently reported by Tsubouchi et al (2013). Previous research has demonstrated that PLLA-degrading bacteria are distributed among the families Bacillaceae, Micromonosporaceae, Streptosporangiaceae, Thermomonosporaceae, Thermoactinomycetaceae (Sukkhum et al, 2009b) and Pseudonocardiaceae .…”
Section: Phenotypic and Phylogenetic Studies Of Plla-degrading Thermomentioning
confidence: 99%
“…L. sacchari LP175 showed substantial growth on NA with added cellulose, inositol, raffinose, rhamnose and sucrose; however, no growth was evident for L. sacchari comb. nov.. Isolates C77, C79, C86, C88, C89, K25 and KT176 showed 99.7% similarity with the filamentous bacteria, Polycladomyces abyssicola JIR-001 T , a novel genus which was recently reported by Tsubouchi et al (2013). Previous research has demonstrated that PLLA-degrading bacteria are distributed among the families Bacillaceae, Micromonosporaceae, Streptosporangiaceae, Thermomonosporaceae, Thermoactinomycetaceae (Sukkhum et al, 2009b) and Pseudonocardiaceae .…”
Section: Phenotypic and Phylogenetic Studies Of Plla-degrading Thermomentioning
confidence: 99%
“…A large group of anaerobic and thermophilic microorganisms have been isolated and studied from the deep-sea, particularly at both hydrothermal vents and sub-seafloor sites, either for their physiological properties or for their potential applications [ 29 , 30 , 31 , 32 , 33 , 34 ]. Representative deep-sea environments, if not in terms of geographical extension but certainly as the most spectacular, are the deep-sea hydrothermal vents.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing (April 2015), with seven new genera, Desmospora , Kroppenstedtia , Lihuaxuella , Marininema , Melghirimyces , Polycladomyces and Shimazuella , the family comprised 13 recognized genera. These bacteria are characterized by the formation of a single, non-stalked spore on the aerial or substrate hyphae, or consecutive spores on straight or branched sporephores (Tsubouchi et al , 2013). Most species of the family are thermophilic, although several members of the genera Seinonella , Mechercharimyces and Shimazuella are mesophilic.…”
mentioning
confidence: 99%